EFEKTIFITAS PENILAIAN MENGGUNAKAN ANTE NATAL RISK QUESTIONNAIRE TERHADAP KEJADIAN DEPRESI POSTPARTUM - Grace Carol Sipasulta; Nurhayati Nurhayati (Poltekkes Kemenkes Kalimantan Timur, 2016)
Mental disorder after Childbirth, was often unknown. The fact that as many as 80% of women experience some mood disorders in time after pregnancy or the postpartum period. This study used a prospective cohort design. This design is intended to determine the effectiveness using of Antenatal Risk Questionnaire (ANRQ) in early detection risk and the incidence of postpartum depression in the setting of Ante Natal Care (ANC). Consecutive Sampling n=138 pregnant women, in third trimester, 33–37 weeks of pregnant, on seven inpatient of Pusat Kesehatan Masyarakat (Puskesmas), Balikpapan city. Data analysis used uni-variate analysis with frequency distribution, analysis bi-variate statistical Mc Nemar tests and Multivariate used Simple Linear Regression Risk Model Factors for confounding variables. By confounding variable controlled, pregnant women with a risk of depression can have a chance to experience postpartum depression 9.5 times compared pregnant women do not risk going depression. Conclusions and suggestions ANRQ tool is easy to use, can be received early psychosocial assessment and effective use of early detection of pregnant women may experience postpartum depression incidence but requires another combination if you want to get more data. Very helpful as a